PENGARUH SISTEM INFORMASI TERHADAP KEJUJURAN LAPORAN KEUANGAN MANAGER: SEBUAH PERSPEKTIF PERILAKU - Warno, Warno; Suedi, Bambang (Sekolah Tinggi Ilmu Ekonomi Semarang, 2010)
This study aimed to tnvestiqate  the influence of information systems for financial reporting manager's honesty.  Based on the agency theory as grand theory, it can be drawn a relationship  between two variables, namely : information  systems and fairness of financial reports to the manager/principal (owner). Based on  theory study, it can be formulated that the consalidated  financial managers were more honest when there are no information  systems; and compared coarse information system with precise information system.